One-Pot Anodic Electrodeposition of Dual-Cation-Crosslinked Sodium Alginate/Carboxymethyl Chitosan Interpenetrating Hydrogel with Vessel-Mimetic Heterostructures - Xuli Li; Yuqing Qu; Yong Zhang; Pei Chen; Siyu Ding; Miaomiao Nie; Kun Yan; Shefeng Li (Journal of Functional Biomaterials)
This study develops a one-pot anodic templating electrodeposition strategy using dual-cation-crosslinking and interpenetrating networks, coupled with pulsed electrical signals, to fabricate a vessel-mimetic multilayered tubular hydrogel. Typically, the anodic electrodeposition is performed in a mixture of sodium alginate (SA) and carboxymethyl chitosan (CMC), with the ethylenediaminetetraacetic acid calcium disodium salt hydrate (EDTA·Na2Ca) incorporated to provide a secondary ionic crosslinker (i.e., Ca2+) and modulate the cascade reaction diffusion process. The copper wire electrodes serve as templates for electrochemical oxidation and enable a copper ion (i.e., Cu2+)-induced tubular hydrogel coating formation, while pulsed electric fields regulate layer-by-layer deposition. The dual-cation-crosslinked interpenetrating hydrogels (CMC/SA-Cu/Ca) exhibit rapid growth rates and tailored mechanical strength, along with excellent antibacterial performance. By integrating the unique pulsed electro-fabrication with biomimetic self-assembly, this study addresses challenges in vessel-mimicking structural complexity and mechanical compatibility. The approach enables scalable production of customizable multilayered hydrogels for artificial vessel grafts, smart wound dressings, and bioengineered organ interfaces, demonstrating broad biomedical potential.